Clinical and neonatal outcomes of intrauterine insemination with frozen donor sperm. (4th July 2018) - Chen, Linjun; Zhu, Lihua; Cai, Changming; Yan, Guijun; Sun, Haixiang
ABSTRACT: This retrospective study evaluated the association between frozen donor sperm used for intrauterine insemination and clinical and neonatal outcomes, including 304 singleton pregnancies resulting from artificial insemination by the husband (AIH) and 173 singleton pregnancies resulting from artificial insemination by a donor (AID). The clinical outcomes for AID showed no increased risk of abortion, ectopic pregnancy or pregnancy complications compared to those for AIH. There were no differences in gender, gestational age or prematurity of live births between the two groups. However, the birthweight of live births from AID was significantly higher than that from AIH. Moreover, the AID group exhibited no increased risk of stillbirths or fetal defects compared to the AIH group. These results indicate that frozen donor sperm did not increase the occurrence of adverse clinical and neonatal outcomes when compared to sperm from the husband. Abbreviations : AID: artificial insemination by a donor; AIH: artificial insemination by the husband; ART: assisted reproduction technology; FET: frozen embryo transfer; IVF: in vitro fertilization; ICSI: intracytoplasmic sperm injection; IUI: intrauterine insemination; LBW: low birth weight